Methicillin resistant Staphylococcus aureus on horses wound - Ahmad Nadzir, Nur Adilah; Zakaria, Zunita; Mohd Adzahan, Noraniza (2015)
Nowadays, Methicillin Resistant Staphylococcus aureus (MRSA) infection is increasingly found in animals including horses, however minimal investigation is recorded in Malaysia. The purpose of this study was to estimate the prevalence of MRSA on the wound of horses in selected stables. Samples were collected from wounds of thirty (30) horses between June 2013 and October 2013. The isolation and identification of MRSA were carried out on selective media (Mannitol Salt agar and Oxacillin Resistant S. aureus agar) and confirmed using series of biochemical tests. The cultures were also tested for presence of nuc species-specific gene. A high proportion of MRSA (66.7%) MRSA were obtained from the samples. Antibiotic sensitivity tests (AST) demonstrated the multi-resistance characteristics of the MRSA cultures.